Ring type and π electron occupancy decides the Li-ion storage properties of Phagraphene: An example of sp2 hybridized carbon structure. (April 2018) - Rajkamal, A.; Sinthika, S.; Andersson, Gunther; Thapa, Ranjit
Abstract: Graphite, a sp 2 hybridized layered material is used as an anode material in commercial Lithium ion batteries (LIB's). It is desirable to improve the Li/C ratio in the sp 2 hybridized carbon allotropes to increase the specific energy capacity. Using First-principles calculations bulk Phagraphene (contains penta-, hepta- and hexa ring) an example of sp 2 hybridized carbon allotropes is identified as a potential high capacity anode material for rechargeable LIB's. The Li adsorption site preference is attributed to the combined effect of the pz electrons of the carbon atoms constituting a ring. It is found that the Li diffusion is favoured during both adsorbed and intercalated state. Bulk-Phagraphene shows desirable negative formation energy, high specific capacity of 558 mAh/g, and stable positive open circuit voltage profile for high Li intercalation. Overall the asymmetry in the pz electron occupancies of the distinct carbon atoms in Phagraphene is identified to be a major contributing factor for the higher activity of Phagraphene as compared to the graphene. This indicates that we can tune the property of sp 2 based carbon structures by changing the π electron environments. Graphical abstract: Image 1